Complimentary Effects of Curcumin for Enhancing Efficacy of Acetylsalicylic Acid against Prostate Cancer - Mohapatra, Tapas Kumar; Mohapatra, Debasish; Subudhi, Bharat Bhusan (Indian Journal of Pharmaceutical Education and Research, 2019)
Background: Prostate cancer is the 6th leading cause of cancer death worldwide. Androgen Deprivation Therapy (ADT) in prostate cancer enhances the risk of Rheumatoid Arthritis (RA). Acetylsalicylic Acid (ASA) can be potentially repurposed against prostate cancer and arthritis. However, its efficacy is low and use is associated with nephrotoxicity as well as gastrotoxicity. Curcumin with reported ability to potentiate anti-inflammatory effects and reduce oxidative stress, can be used as a complementary therapy to enhance efficacy of ASA against prostate cancer and arthritis. This can also minimise ASA induced nephrotoxicity and gastrotoxicity. Aim and Objectives: To evaluate the ability of curcumin to enhance efficacy of ASA against prostate cancer, arthritis while minimising its adverse effects. Methods: In-vitro anticancer activity was assessed in DU-145 (Androgen-independent) and LNCaP (Androgen-dependent) cells. Effect against arthritis was evaluated in complete Freund’s adjuvant (CFA) induced arthritis model in rats. Biochemical factors, radiology and histopathology were examined. Protection against kidney dysfunction and ulceration was determined. Results: Curcumin on co-administration with ASA (ASA+Cur) (25 µM + 25 µM) showed higher efficacy against DU-145 and LNCaP cell model. This co-use showed significant (p<0.001) inhibition of arthritis index (AI). The erythrocyte sedimentation rate (ESR) and rheumatoid factor (RF) were significantly (p<0.001) decreased from their elevated level. It also reduced tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β) and interleukin 6 (IL-6) at the molecular level. While it showed moderate gastro-protection, there was no adverse effect on kidney functions. Conclusion: Curcumin seems to enhance the effect of ASA against androgen dependent as well as androgen independent prostate cancer while reducing arthritis. Simultaneously, it reduces ASA induced gastrotoxicity and prevents nephrotoxicity.
Keywords: Acetylsalicylic acid; Androgen deprivation; Prostate cancer; Arthritis index; Gastric ulcer